Effect of silymarin and its polyphenolic fraction on cholesterol absorption in rats - Sobolová, Lucie; Škottová, Nina; Večeřa, Rostislav; Urbánek, Karel (Pharmacological research, 2006)
This study evaluated the influence of silymarin (SM) and polyphenolic fraction (PF) of silymarin on cholesterol absorption in rats fed on high cholesterol diet (HCD). HCD induced a remarkable increase in hepatic, plasma, VLDL and LDL cholesterol, a decrease in HDL cholesterol and an elevation in triacylglycerol (TAG) levels in plasma, VLDL and in the liver. SM and PF were administered as dietary supplements (1.0%) in HCD for 18 days. Intestinal cholesterol absorption was measured by dual-isotope plasma ratio method, which calculates percent of cholesterol absorption from the ratio of two labelled cholesterol doses, one given intragastrically (14C) and one intravenously (3H). Silymarin and PF significantly reduced cholesterol absorption in rats fed on HCD and caused significant decreases in plasma and VLDL cholesterol and content of cholesterol and TAG in the liver. The level of HDL cholesterol was significantly increased after silymarin, but not after administration of PF. The levels of TAG in plasma and VLDL were not affected by either silymarin or PF. These results suggest that the inhibition of cholesterol absorption caused by silymarin and its polyphenolic fraction could be a mechanism contributing to the positive changes in plasma cholesterol lipoprotein profile and in lipid content in liver.
Keywords: intestinální absorpce; Liver; financování organizované; flavonoidy; Animals; Antioxidants; Intestinal Absorption; játra; lipoproteiny; cholestyraminová pryskyřice; fenoly; triglyceridy; Flavonoids; lipoproteiny VLDL; Phenols; Silymarin; Triglycerides; cholesterol dietní; azetidiny; Cholestyramine Resin; Financing, Organized; Male; silymarin; antioxidancia; krysa rodu Rattus; Lipoproteins; zvířata; mužské pohlaví; Cholesterol, Dietary; Rats; Lipoproteins, VLDL; Azetidines